PENGARUH METODE LATIHAN SAQ ( SPEED, AGILITY, QUICKNES) TERHADAP KEMAMPUAN LARI SPRINT 100 METER DALAM KEGIATAN ESKTRAKULIKULER ATLETIK SISWA SMPN 3 CIKARANG UTARA - Pangestu, Aldi Firman; Resty Gustiawati; Rolly Afrinaldi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Athletics in junior high schools can be integrated as part of extracurricular activities to form athletes' competencies and skills as a whole with the aim of achieving achievements. The SAQ (speed, agility, and quickness) training method has an important role in increasing running speed which is a key aspect in sprinting. This study uses an experimental method that can be defined as a systematic method to build relationships that contain cause-and-effect phenomena. This experimental study was conducted using pretest and posttest tests after 16 SAQ training treatments. The results of this study refer to the results of nonparametric statistical tests using the Wilcoxon signed ranks test. Based on the results of the Wilcoxon test, the significance value is 0.008 <0.05, the hypothesis is accepted that there is an effect of the speed, agility and quickness (SAQ) training method on students' 100-meter sprint ability in athletic extracurricular activities at SMPN 3 Cikarang Utara.